Newborn Screening for Spinal Muscular Atrophy in China Using DNA Mass Spectrometry - Lin, Yiming; Lin, Chien-Hsing; Yin, Xiaoshan; Zhu, Lin; Yang, Jianbin; Shen, Yuyan; Yang, Chiju; Chen, Xigui; Hu, Haili; Ma, Qingqing; Shi, Xueqin; Shen, Yaping; et al. (Frontiers in Genetics, 2019)
Background: Spinal muscular atrophy (SMA) is the most common neurodegenerative disorder and the leading genetic cause of infant mortality. Early detection of SMA through newborn screening (NBS) is essential to selecting pre-symptomatic treatment and ensuring optimal outcome, as well as, prompting the urgent need for effective screening methods. This study aimed to determine the feasibility of applying an Agena iPLEX SMA assay in NBS for SMA in China. Methods: We developed an Agena iPLEX SMA assay based on the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF), and evaluated the performance of this assay through assessment of 167 previously-genotyped samples. Then we conducted a pilot study to apply this assay for SMA NBS. The SMN1 and SMN2 copy number of screen-positive patients were determined by multiplex ligation-dependent probe amplification analysis (MLPA). Results: The sensitivity and specificity of the Agena iPLEX SMA assay were both 100%. Three patients with homozygous SMN1 deletion were successfully identified and conformed by MLPA. Two patients had two SMN2 copies, which was correlated with severe SMA type I phenotype; both of them exhibited neurogenic lesion and with decreased muscle power. Another patient with four SMN2 copies, whose genotype correlated with milder SMA type III or IV phenotype, had normal growth and development without clinical symptoms. Conclusions: The Agena iPLEX SMA assay is an effective and reliable approach for population-based SMA NBS. The first large-scale pilot study using this assay in the Mainland of China showed that large-scale implementation of population-based NBS for SMA is feasible.